Dental students, interns, and junior dentists' awareness and attitude toward the inferior alveolar nerve block technique and related failure - Salah Sakka; Nasser Raqe Alqhtani; Abdullah Saad Alqahtani; Abdullah Bin Nabhan; Mohamed Kamal Eid; Maram Alagla; Khalid Alfaifi; Mohammad Zakaria Nassani (Elsevier, 2024)
Background/purpose: Exploration of early practicing dental professionals' awareness and attitude toward inferior alveolar nerve block IANB will directly inform efforts to improve clinical practices and ensure patient safety. The aim was to highlight the students, interns, and junior dentists' awareness and attitude toward the IANB, failure, and related complications in the Kingdom of Saudi Arabia (KSA). Materials and methods: An open web-based survey prepared according to the Checklist for reporting results of Internet e-surveys CHERRIES recommendations was designed and carried out across different regions of the KSA. The questionnaire was composed of four main sections including the participant's details, and qualifications; inferior alveolar nerve block delivery; participants' education, and training-related questions; and attitudes toward proposed solutions to overcome the related failure and complications. Results: 262 participants completed the questionnaire (94 dental students, 79 interns, and 89 junior dentists). There was a significant difference in the following findings: males performed IANBs more frequently than females (P < 0.05); females, students, and private practice/University type showed less attendance to workshops and seminars on IANB with more need for training (P < 0.05); females were more in agreement with ''continuous education courses'' and ''workshops done by specialists'' to propose solutions to overcome IANB failure (P < 0.05). The multivariate logistic regression analysis showed that qualification and attendance of a training course were strong predictors of participants' readiness to manage IANB complications (P < 0.05). Conclusion: The findings emphasize how crucial it is for early dental practitioners to participate in continuing professional development programs to enhance their capacity to administer IANB and handle complications.